Inhibiting ROS-TFE3-dependent autophagy enhances the therapeutic response to metformin in breast cancer. (3rd August 2018) - Tan, Miduo; Wu, Anshang; Liao, Ni; Liu, Min; Guo, Qiong; Yi, Jiansheng; Wang, Taoli; Huang, Yan; Qiu, Bo; Zhou, Wei
Abstract: Autophagy modulation is a potential therapeutic strategy for breast cancer, and a previous study indicated that metformin exhibits significant anti-carcinogenic activity. However, the ability of metformin to induce autophagy and its role in breast cancer cell death remains unclear. In this study, we exposed MCF-7 cells to different concentrations of metformin (2.5, 5, and 10 mM) for 48 h, and metformin-induced significant apoptosis in the MCF-7 cells. The expression levels of CL-PARP (poly(ADP-ribose) polymerase 1) and the ratio of BAX to BCL-2 were significantly increased. In addition to apoptosis, we showed that metformin increased autophagic flux in MCF-7 cells, as evidenced by the upregulation of LC3-II and downregulation of P62/SQSTM1. Moreover, pharmacological or genetic blocking of autophagy increased metformin-induced apoptosis, indicating a cytoprotective role of autophagy in metformin-treated MCF-7 cells. Mechanistically, metformin-induced TFE3 (Ser321) dephosphorylation activated TFE3 nuclear translocation and increased of TFE3 reporter activity, which contributed to lysosomal biogenesis and the expression of autophagy-related genes and, subsequently, initiated autophagy in MCF-7 cells. Importantly, we found that metformin triggered the generation of reactive oxygen species (ROS) in MCF-7 cells. Furthermore, N -acetyl-l -cysteine (NAC), a ROS scavenger, abrogated the effects of metformin on TFE3-dependent autophagy. Notably, TFE3 expression positively correlated with breast cancer development and poor prognosis in patients. Taken together, these data demonstrate that blocking ROS-TFE3-dependent autophagy to enhance the activity of metformin warrants further attention as a treatment strategy for breast cancer.